Telling the Untellable: Trauma and Sexuality in Big Little Lies - O. Réti, Zsófia (Hungarian Journal of English and American Studies, 2020)
The problem of sexual violence, including rape, domestic assault, sexual harassment, and molestation has recently become a topical issue both in public discourse and popular culture. The unspoken individual traumas have found their way to the world of TV series, such as HBO’s mini-series Big Little Lies. The essay explores the unique ways in which the television series treats sexuality and personal traumas. It argues that while by no means can it be regarded as a soap opera, Big Little Lies occasionally uses and rewrites the genre-specific codes of this traditionally low-prestige television genre intended for women to alter the representation of individual traumas in popular culture. The use of flashbacks and involuntary repetition as narrative elements along with the retrospective framework of a criminal investigation make the serial form much suited to examine individual traumas. The television series attempts the almost impossible: to speak of the trauma’s unspeakability, and simultaneously it seeks to maintain its high viewership. (ZsOR)